Pluralisme Hukum: Relasi Hukum Negara Dan Hukum Adat Pada Masyarakat Adat Malind-Anim - Maleakhi Samuel Pasalli; Adhitiya Augusta Triputra (Jurnal Restorative Justice, 2026)
Abstract This research aims to examine the construction of legal pluralism in the relation between state law and Malind Anim customary law within Law Number 21 of 2001 concerning Special Autonomy for the Papua Province as well as its amendment, Law Number 2 of 2021 concerning the Second Amendment to Law Number 21 of 2001 concerning Special Autonomy for the Papua Province (Papua Special Autonomy Law). Although the Papua Special Autonomy Law broadly recognizes customary law, this research finds a paradigmatic tension between the normative ideal of strong legal pluralism and the regulatory reality characterized by weak legal pluralism. Utilizing normative legal research methods with statute and conceptual approaches, this study dissects Law Number 21 of 2001 jo. Law Number 2 of 2021 along with its implementing regulations (Perdasus). The results indicate that the legal construction built by the state separates protection into two main clusters: political rights attached to Indigenous Papuans (Orang Asli Papua or OAP) and property rights as well as jurisdiction attached to Customary Law Communities (Masyarakat Hukum Adat or MHA). However, the legality of rights in this second cluster is not purely autonomous (self-executing) but relies on procedural formalization through Perdasus. Analysis of Perdasus Number 20 of 2008 and Perdasus Number 23 of 2008 demonstrates that these derivative legal products of the Papua Special Autonomy Law actually operationalize the logic of legal centralism which reduces the autonomy of indigenous communities, both by limiting the jurisdiction of customary courts and facilitating the release of customary communal rights (hak ulayat), which are at times inconsistent with the cosmological philosophy of the Malind- Anim indigenous people, namely Anim Ha. This proves that special autonomy in Papua is essentially a form of decentralized legal centralism, wherein the national legal system remains the superordinate that subordinates customary law.